The Deep Structure of Situated Thinking in Professionals - Lynda Thomas Goodfellow; Thomas Valentine (Adult Education Research Conference, 2002)
This study explicates Critical Thinking (CT) in the respiratory care profession. An exploratory factor analysis was performed and seven measured CT behaviors were narrowed to two factors. A cluster analysis followed and three groups of practitioners were found. This empirical typology considerably expands the conception of CT in the professions.